Статистика населення в Україні в 1920–1930-ті роки - Гладун, О.М.; Рудницький, О.П. (Інститут демографії та соціальних досліджень НАН України, 2009)
У статті розглянуто стан в Україні складових статистики населення (природний рух, міграція, розрахунки, переписи населення) в період між Першою та Другою світовими війнами; оцінена повнота та якість даних, що є в наявності; зроблено висновок про принципову можливість їх використання для проведення демографічних досліджень. В статье рассмотрено состояние в Украине составляющих статистики населения (естественное движение, миграция, расчеты, переписи населения) в период между Первой и Второй мировыми войнами; оценена полнота и качество имеющихся данных; сделан вывод о принципиальной возможности их использования для проведения демографических исследований. The biggest lost of population in Ukraine during non-war periods was observed between first and second World Wars. It was caused by violent collectivization, Famine, repressions. Research of these losses requires corresponding statistical information regarding demographic processes. The goal of the article is the research of population statistics status in interwar period and general estimation of quality and completeness of available demographic data. The article reviews peculiarities of registration and processing of information in Ukraine regarding
natural population movements. During research of statistical investigation of population migration processes big attention was paid to completeness of the registered data. Currently
badly studied heritage of population number and structure calculations was presented. Special attention was paid to population censuses of 1926, 1937 and 1939, – as to the most important
source of data for estimation of Ukrainian population lost in the interwar period. The article covers the process of institutional development of demographic statistics in Ukraine. A conclusion was made that available population statistics data requires some corrections, which acceptance would allow this data to be used for various demographic researches.